Pola Asuh Anak yang Ditinggal Merantau: Studi Kasus pada Siswa Kelas V SD Negeri 1 Sendang Kulon Kendal - Wahyu Adiningsih; Eka Sari Setianingsih; Khusnul Fajriyah (STKIP Andi Matappa Pangkep, 2022)
This research is motivated by the lack of awareness of parents about the importance of providing effective parenting for children, especially for children who are left to wander and to find out how the learning outcomes of children who are left wandering. This type of research is descriptive qualitative with a descriptive percentage approach. The subjects of the study were fifth grade students of SD Negeri 1 Sendang Kulon whose parents went abroad and parents or guardians of students who took care of their children at home. Based on data collection using interviews, observations, questionnaires, and documentation, the results showed that there were three parenting patterns applied by parents or guardians to students who were left to wander, including 71.4% of the parenting styles tended to be democratic, 14, 3% of parenting tend to be authoritarian, and 14.3% of parenting tend to be permissive. Students with democratic parenting tend to have good and very good learning outcomes. Students with authoritarian parenting tend to have good learning outcomes. And students with permissive parenting tend to have good learning outcomes. The conclusion of this study is that giving good parenting to children can make it easier to improve children's learning outcomes.